Daridorexant: A New Dual Orexin Receptor Antagonist for Insomnia. (October 2022) - Onge, Erin St.; Phillips, Bradley; Rowe, Casey
Objective: To review the safety, efficacy, and tolerability of daridorexant in treating insomnia characterized by difficulties with sleep onset and/or sleep maintenance in adult patients.Data Sources: A literature search was performed through PubMed using the following key terms: daridorexant, ACT-541468, orexin, insomnia, and sleep .Study Selection and Data Extraction: Selected articles included those which described clinical studies of the pharmacokinetics, efficacy, safety, or tolerability of daridorexant.Data Synthesis: Daridorexant works through antagonism of the dual orexin receptor. It is the third agent in this class of medications approved by the U.S. Food and Drug Administration (FDA). Daridorexant, at a dose of 25 mg to 50 mg, was shown to be effective in improving sleep parameters in phase 3 clinical studies and was well tolerated. Adverse event rates from phase 2 and 3 clinical trials were low with fatigue, nasopharyngitis, gait disturbance, somnolence, diarrhea, and headache most commonly reported.Conclusions: All currently available agents for treating insomnia have received a "weak" recommendation in the clinical practice guidelines, including the dual orexin receptor antagonist class of medications. Initial data suggest that with routine use daridorexant does not impair next day functioning, a common issue with other agents used to treat insomnia. In addition, daridorexant appears to be as safe and effective in treating insomnia in patients of all ages including those ≥65 years of age.